1997
DOI: 10.1074/jbc.272.41.25483
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Recombinant REGα, REGβ, and REGγ Proteasome Activators

Abstract: Full-length cDNAs for three human proteasome activator subunits, called REG␣, REG␤, and REG␥, have been expressed in Escherichia coli, and the purified recombinant proteins have been characterized. Recombinant ␣ or ␥ subunits form heptameric species; recombinant ␤ subunits are found largely as monomers or small multimers. Each recombinant REG stimulates cleavage of fluorogenic peptides by human red cell proteasomes. The pattern of activated peptide hydrolysis is virtually identical for REG␣ and REG␤. These two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
202
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(213 citation statements)
references
References 68 publications
11
202
0
Order By: Relevance
“…Most cellular proteins are degraded through the 26S proteasome after ubiquitination, a way for 26S to recognize proteins that need to be degraded. The alternative proteasomal activator, REG (also known as 11S proteasome) activates the 20S proteasome in an ATP-independent manner and is primarily responsible for ubiquitin-independent protein degradation (Realini et al, 1997). REGα/β can be induced by interferon(IFN)-γ and play an important role in MHC class I antigen presentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most cellular proteins are degraded through the 26S proteasome after ubiquitination, a way for 26S to recognize proteins that need to be degraded. The alternative proteasomal activator, REG (also known as 11S proteasome) activates the 20S proteasome in an ATP-independent manner and is primarily responsible for ubiquitin-independent protein degradation (Realini et al, 1997). REGα/β can be induced by interferon(IFN)-γ and play an important role in MHC class I antigen presentation.…”
Section: Discussionmentioning
confidence: 99%
“…The 19S activator binds to 20S proteasome to form the 26S proteasome in an ATP-dependent manner, which mainly performs degradation of proteins in a ubiquitindependent manner. In contrast, the REG activates the 20S proteasome in an ATP-independent manner and is primarily responsible for ubiquitin-independent protein degradation (Realini et al, 1997). There are three REG homologs, called α, β and γ.…”
Section: Introductionmentioning
confidence: 99%
“…It remains to be seen whether a mixture of recombinant PA28␣ and PA28␤ forms a heterohexameric or heteroheptameric complex. Realini et al (1997) reported that recombinant REG␤ and REG␥ (equivalent to PA28␤ and PA28␥, respectively) are capable of stimulating the peptidase activities of the 20S proteasome. Contrary to these results, Song et al (1997) reported that PA28␤ alone has no detectable effect on the peptidase activities of the 20S proteasome but that it appreciably reduces the K m without affecting the V max for the PA28␣-activated proteasome, suggesting an important functional interaction between PA28␣ and PA28␤.…”
Section: The Pa28 Complexmentioning
confidence: 99%
“…Purification of the 20 S proteasome from T. brucei procyclic form cells was carried out as previously described (33). The human 20 S proteasome, purified from outdated human blood by previously described methods (34), was a kind gift from Prof. Martin Rechsteiner of the University of Utah.…”
Section: T Brucei Cultures and 20 S Proteasome Purification-t Brucementioning
confidence: 99%